International law and cannabis : regulation of cannabis cultivation for recreational use under the UN Narcotic Drugs Conventions and the EU Legal Instruments in Anti-Drugs Policy. Piet Hein van Kempen, Masha Fedorova. - Kempen, P. H. P. H. M. C. van (Piet Hein P. H. M. C.); Fedorova, Mascha (Intersentia, 2019)
See also volume I, Regulation of Cannabis Cultivation for Recreational Use under the UN Narcotic Drugs Conventions and the EU Legal Instruments in Anti-Drugs Policy, here. Both volumes can also be purchased as a set here. What legal avenues do states have to regulate cannabis cultivations and trade for recreational use? This question has generated heated discussions in various societies, in political and academic discourses. Several states are considering adjusting or have adjusted their legal and policy approaches towards a more lenient regulation of cannabis cultivation and trade for the recreational user market. Seen from the perspective of relevant United Nations narcotic drugs conventions, the legal avenues for regulation are virtually non-existent. This book takes an innovative approach to this issue and approaches the possibility for regulation of cannabis for recreational use from the perspective of positive human rights obligations. To what extend can regulation of cannabis for recreational use, for the sake of health, safety and crime control, be considered a positive human rights obligation resulting from the right to health, the right to life, the right to physical and psychological integrity and the right to privacy? From the subsequent conclusions, a second pertinent question arises: what hierarchical relationship, if any, exists between these positive human rights obligations and the obligations arising from the UN drugs conventions? Through an in-depth and systematic analysis of relevant international human rights law and public international law, this book presents the steps, assumptions and conditions that are relevant if a state were to decide, on the basis of the incumbent positive human rights obligations, to permit cannabis cultivation and trade for the recreational user market under regulation. PIET HEIN VAN KEMPEN, LLM, PhD, and MASHA FEDOROVA, LLM, PhD, are Full Professors of Criminal Law and Criminal Procedure Law at the Faculty of Law of Radboud University, Nijmegen, the Netherlands.